Barriers to support for new graduated nurses in clinical settings: A qualitative study. (February 2016) - Ebrahimi, Hossein; Hassankhani, Hadi; Negarandeh, Reza; Azizi, Azim; Gillespie, Mark
Summary: Background: New graduated nurses often find the transition to registered nurse a traumatic experience and studies suggest that within some countries this process is inadequately supported. The reasons for this inadequacy remain unclear. Objectives: The current study was conducted to identify barriers impeding the provision of support to new graduated nurses in clinical settings within Iran. Methods and participants: This is a qualitative study conducted through unstructured and semi-structured interviews with 18 licensed nurses (experienced nurses) recruited through purposive sampling. Data were collected at various hospital centers in Iran. All interviews were recorded and transcribed and analysis was completed through the use of content analysis. Results: Barriers to support new graduated nurses included a lack of support-seeking behaviors, management weaknesses, ineffective communication, personal characteristics, and cultural barriers. Conclusions: Understanding the problems and barriers likely to prevent goal attainment is an important step toward reaching those goals. The present study provides a greater and more focused understanding of the barriers impeding the support of new graduated nurses within clinical settings. These barriers mainly include deficiencies in the organizational structure, management, and personal characteristics of colleagues and new graduated nurses. This study will have been a successful undertaking if it can help resolve these barriers. Highlights: Use of obsolete methods by managers and older nurses. Older nursing perspective revealed lack of understanding about new graduated nurse's transition and needs those in this stage. Emphasizes essential role of culture of society as a barrier to support of them. The present study provides a greater and more focused understanding of the barriers impeding supporting new graduated nurses in clinical settings.